Cultural Erosion and Moral Crisis in Nigerian Tertiary Institutions: A Religious and Cultural Appraisal of Students’ Week and Sign-Out Practices - Mathew Stephen; Ibrahim Abba Tukur; Hussaini Said Yusuf; Lydia Daniel (Darul Yasin Al Sys, 2026)
This paper critically examines the growing moral and cultural decline associated with Students’ Week and Sign-Out Day celebrations in Nigerian tertiary institutions. Originally designed as moments of academic reflection and thanksgiving, these events have increasingly become characterized by indecent dressing, public immorality, and disregard for both African and religious values. Drawing from Cultural Erosion Theory and Social Learning Theory, the study analyzes how globalization, social media, and peer influence have contributed to the erosion of indigenous African moral codes and the normalization of immoral behaviours among students. It further explores the roles of religion, school authorities, and society in restoring moral integrity and cultural identity. The findings reveal that moral decay on campuses is not merely a behavioural problem but a symptom of deep-seated cultural disorientation and ethical neglect. The paper recommends a holistic moral reformation involving religious institutions, educational authorities, and cultural organizations to redefine Students’ Week and Sign-Out celebrations as avenues for thanksgiving, decency, and communal responsibility. It concludes that genuine celebration in African and religious contexts must uphold modesty, gratitude, and moral order rather than indulgence and excess.